Analisis Kepuasan Wisatawan terhadap Atribut Pariwisata Syariah di Kawasan Wisata Iboih, Kota Sabang (Menggunakan Metode Importance-Performance Analysis) - M. Rizki Setiawan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
Sharia-based tourism becomes a new trend in the dynamic tourism industry development. Various efforts should be carried out to meet the requirement and to increase tourist satisfaction in enjoying sharia-based tourism. This study is aimed to measure tourist satisfaction range about attributes of sharia-based tourism existing in the tourism area, Iboih, Sabang. Another purpose of this study is to find out which attributes that should be prioritized to be reinforced. The data of this study was collected by distributing questionnaires to 154 tourists. After obtaining the data, the data was analyzed by using importance-performance analysis method, supported by the data from interview and observation. The result of this study showed that the satisfaction index to attributes sharia-based tourism in Iboih, tourism area, was 3,972 with the amount of conversion score was 79,44. The number previously mentioned indicated that the range of satisfaction received by tourists was in the satisfied category. Besides, there were 6 attributes that should be prioritized to be reinforced. Those six attributes were 1) cleaned, holy, and appropriate worshiped facilities around tourist objects. 2) The attainability of worship facilities in the lodgment (i.e Sajadah, mukena, Al-Quran, and purified facilities. 3) proper, cleaned and holy place to do shalah in the lodgment. 4) Cleaned and good sanitation system in the lodgment area. 5) Halal certificate on the sold food and beverage. 6) Cleaned and good sanitation in the restaurant area.